Acculturation, social exclusion and resistance: Experiences of young Moroccans in Italy. (September 2018) - Cicognani, Elvira; Sonn, Christopher C.; Albanesi, Cinzia; Zani, Bruna
Abstract: This qualitative study examines how young people of Moroccan descent in Italy construct their social identities and make sense of acculturation experiences. Twenty nine Moroccan young people, fourteen males and fifteen females (16–23 years old) took part in five focus groups. Thematic analyses of data indicated that participants have to navigate different identity categories in the host country, including Muslim, Moroccan, and migrant, which are often used to construct them as not belonging. They use different strategies to negotiate experiences of prejudice and exclusion including; "Italy is not my home… it is other people's home": Accommodating an outsider status, turning critically towards one's community, claiming an insider status: Feeling Italian, Creating activist identities: Becoming bridge builders. In the absence of legal status, participants conceived citizenship as respecting Italian laws and norms, accommodating their status and position, but making claims based on being and feeling as belonging – cultural citizenship. By using a liberation orientation, our analysis shows the political nature of acculturative integration in a context that denies citizenship as a legal status. These political aspects include deconstructing exclusionary dominant group narratives and forming identities of resistance that are important to their claims for recognition and belonging. We discuss the findings with reference to ways in which researchers and activists can support the activities of young people of immigrant background.